PENGARUH IKLIM SOSIAL SEKOLAH TERHADAP SIKAP BELAJAR EKONOMI IPS SMA NEGERI 01 SUNGAI PINYUH - Kadariah Kadariah; Bambang Genjik; Muhammad Basri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims : (1) school social climate of State High School 01 Sungai Pinyuh Mempawah Regency, (2) the economic learning attitude of social studies students at State High School 01 Sungai Pinyuh Mempawah Regency, (3) the influence of the school’s social climate on the economic learning attitudes of social studies students at State High School 01 Sungai Pinyuh Mempawah Regency. The research approach used is quantitaive in the form of a survey. The sample of the study used a sample random sampling technique, totaling 71 respondents. The technique used in data collection is a questionnaire technique to the research sample assited by google form. The data analysis of ths study used simple linear regression assisted by IBM SPSS 23 with the results of the study showing that: (1) positive and conducive school social climate according to the students perception is included in the very high category with the interpretation score of 85.59%; (2) the learning sttitude of students is very good and positive with the interpretation score of 79.56%; (3) there is significant positive effect of the schools social climate on students economic learning attitudes as indicated by sig.alpha 0.000<0.05 and the coefficient of determination is 0.397.Keywords: School Social Climate and Learning Attitude